Enhancement of the Technology for Live Tularemia Vaccine Production - O. A. Volokh; A. V. Komissarov; M. V. Antonycheva; O. A. Lobovikova; N. G. Avdeeva; N. I. Vakhrushina; N. P. Mironova; D. N. Bibikov; A. K. Nikiforov (Проблемы особо опасных инфекций, 2016)
Objective of the study was to develop and test new biotechnological approaches for live tularemia vaccine production.Materials and methods: Francisella tularensis 15 NIIEG strain was used as producer-strain; Francisella tularensis 503 strain – as test infecting one. Producer strain was cultivated on solid and liquid nutrient media. Tangential ultrafiltration was performed with the help of microfiltration module “Viva-flow”. Lyophilization was conducted using drying installation – Free Zone 2.5 L.Results and discussion: Application of the designed liquid nutrient medium on the basis of enzymatic fibrin hydrolysate and submerged cultivation of the producer-strain has allowed for a significant biomass yield increment. At the stage of tularemia microbe culture concentration via microfiltration through filtering membranes with pore size of 0.2 μm, in the mode of tangential liquid flow, increased has been the content of microbe cells; the nutrient media residues – removed. Comparative analysis of the obtained in accordance with experimental technique laboratory series of the vaccine and commercial preparation of live tularemia vaccine has demonstrated their conformity with the specific normative properties. It is established that application of modified liquid nutrient medium, submerged cultivation conditions, methods of biomass concentration and separation has no negative influence on the main properties of live tularemia vaccine and will provide for considerable produce-ability increase in the future.